Prevalence of glucose-6-phosphate dehydrogenase (G6PD) deficiency in neonates in Bunda Women's and Children's Hospital, Jakarta, Indonesia - Risma Kerina Kaban; Veronica Wijaya (Indonesian Pediatric Society, 2011)
Background Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most connnon enzyme deficiency in the world. Itis a risk factor for hyperbilirubinemia in neonates, which can cause serious complications such as bilirubinô€—induced encephalopathy or kernicterus. WHO recommends universal neonatal screening for G6PD deficiency when the frequency exceeds 3ô€—5% of male newborns.Objective To assess the prevalence of G6PD deficiency among neonates in Bunda Women and C hildren Hospital (Bunda WCH), Jakarta, in order to detennine if there is a need for routine G6PD neonatal screening.Methods This is a cross-sectional and retrospective study; infants' data were obtained from medical records. From January 2009 to May 2010, all neonates in Bunda WCH were screened for G6PD deficiency on the yd day of life. Blood samples were collected using filter papers. We considered a result to be nonnal if it exceeded 3.6 U/g Hb.Results A total 1802 neonates were screened. We found 94 neonates (5.2%) with G6PD deficiency. Out of 943 males, 59 (6.26%) were G6PD deficient, and out of 859 females, 35 (4.07%) were G6PD deficient. We observed that prevalence of G6PD deficiency according to sex distribution was significantly higher in males than females (6.26% vs. 4.07%, P=0.037). There was no significant difference in the risk for severe hyperbilirubinemia between the G6PD deficient infants and the nonnal infants (P=0.804).Conclusions The frequencies of G6PD deficiency were 6.26% of male neonates and 4.07% of female neonates. We recommend universal neonatal screening for G6PD deficiencies in Jakarta since our findings exceed the WHO recommendation for routine testing.